Methods of behavioral testing in dogs: a scoping review and analysis of test stimuli - Moser, Ariella Y.; Welch, Mitchell; Brown, Wendy Y.; McGreevy, Paul; Bennett, Pauleen C. (Frontiers in Veterinary Science, 2024)
BackgroundBehavioral testing is widely used to measure individual differences in behavior and cognition among dogs and predict underlying psychological traits. However, the diverse applications, methodological variability, and lack of standardization in canine behavioral testing has posed challenges for researchers and practitioners seeking to use these tests. To address these complexities, this review sought to synthesize and describe behavioral testing methods by creating a framework that uses a “dog-centric” perspective to categorize the test stimuli used to elicit responses from dogs.MethodsA scoping review was conducted to identify scientific literature that has reported behavioral testing to assess psychological traits in dogs. Five online databases were systematically searched. Following this, an inductive content analysis was conducted to evaluate and summarize the behavioral testing methods in the literature.ResultsA total of 392 publications met the selection criteria and were included in the analysis, collectively reporting 2,362 behavioral tests. These tests were individually evaluated and categorized. Our content analysis distinguished 29 subcategories of behavioral testing stimuli that have been used, grouped into three major categories: human-oriented stimuli; environmental stimuli; and motivator-oriented stimuli.ConclusionDespite the methodological heterogeneity observed across behavioral testing methods, our study identified commonalities in many of the stimuli used in test protocols. The resulting framework provides a practical overview of published behavioral tests and their applications, which may assist researchers in selecting and designing appropriate tests for their purposes.